THE ASSOCIATION BETWEEN WORKPLACE READINESS AND INDIVIDUAL CONTROL MEASURES WITH INFECTIOUS DISEASE OUTCOME - Yasin, Siti Munira; Taib, Khairul Mizan; Muzaini, Kamarulzaman; Ismail, Nurhuda; Abdullah, Nik Nairan; Masngut, Mohd Izwan; Nozmi, Noramira; Hair, Ahmad Fitri Abdullah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Workplace practices and individual control measures in occupational safety and health may play a role in infectious disease outcomes. Understanding these factors helps mitigate risks and improve on the disease outcomes. This study aims to identify factors related to infectious disease outcome with regards to occupational health and safety workplace practices and workers individual control measures. This study employed a cross-sectional design involving 13 states and 3 federal territories in Malaysia. A self-administered locally tool was distributed online to 373 workers. The questionnaire consisted of three domains: the sociodemographic section, workplace readiness, and individual control factors. Most of the workers were Malaysian (98.1%), blue-collar workers (75.6%), male (59.8%), and married (70.5%). Most workers perceived adequate workplace policies, although ventilation was less agreed upon. Multivariable regression analysis showed higher disease outcome in workplaces with reactive measures as compared to proactive strategies like early disease screening upon suspected cases. In addition, workers who understood their employer’s health-related responsibilities, had lung-related conditions like asthma, or had received training on proper PPE usage were less likely to have infectious diseases. Understanding the employer responsibilities, good workplace policies, and PPE training are good strategies for infectious disease prevention.